Scientific problem finding in gifted fifth-grade students - Hoover, Steven M. (Roeper review, 1994)
This article presents the results of a study focusing on the scientific problem finding behavior of a group of fifth-grade gifted students. Scientific problem finding was defined for this study as responses to an instrument designed to assess the subjects' abilities to formulate hypotheses given a realistic situation. Based upon previous research with this construct, the author explores the relationship of scientific problem finding to a measure of creativity and a measure of the subjects' tolerance for ambiguity. In addition, comparisons are made between fifth-grade and ninth-grade gifted subjects on their ability to formulate hypotheses. As with a previous study, no differences are found between males and females on scientific problem finding. There are a few significant correlations between a measure of creativity and the ability to formulate hypotheses, and significant differences are found between the age groups on the ability to formulate hypotheses. Implications of the study for future research are presented in the context of a model of problem finding behavior among gifted students.